12.0k views
3 votes
Does anyone know how to solve this??

Does anyone know how to solve this??-example-1
User Sigmus
by
5.0k points

2 Answers

5 votes
I think we are doing the same assignment
User Solvemon
by
5.9k points
1 vote

Answer:

a) (f + g)(x) = x² - 2x + 3x - 4 = x² + x - 4

domain: x E R

b) (f - h)(x) = x² - 2x - ( - 2x + 1) = x² - 1

domain: x E R

c) (f.g)(x) = (x² - 2x)(3x - 4) = 3x³ - 10x² + 8x

domain: x E R

d)


( (h)/(f) )(x) = \frac{ - 2x + 1}{x {}^(2) - 2x}

domain: x E R\{0; 2}

User Juanferrer
by
4.7k points